The Catholic Church and Technological Progress: Past, Present, and Future - Green, Brian P. (Religions, 2017)
Over 2000 years the Catholic Church has slowly developed a posture towards technology which is predominantly techno-optimist and techno-progressive, and yet the Church does not have this reputation today. Concomitantly, Church institutions and individuals have made crucial contributions to the advance of science and technology, yet despite this practical effort to better human development, Christian theology has been remarkably uninterested in the subject of technology. This lack of interest is no longer tenable; scholars of religion and theologians should seriously engage technology because it is empowering humanity in ways that were previously reserved only for gods. This blind spot has not only hampered the Church's ability to understand itself and our world, but also impeded the ability of the Church to fulfill its mission. Pope Francis's 2015 encyclical Laudato Si has begun to address this neglect, but is best understood in the context of Christian history, not only as written, but more so as practiced.